Gut mucosa alterations and loss of segmented filamentous bacteria in type 1 diabetes are associated with inflammation rather than hyperglycaemia. Issue 2 (16th February 2021) - Rouland, Matthieu; Beaudoin, Lucie; Rouxel, Ophélie; Bertrand, Léo; Cagninacci, Lucie; Saffarian, Azadeh; Pedron, Thierry; Gueddouri, Dalale; Guilmeau, Sandra; Burnol, Anne-Françoise; Rachdi, Latif; Tazi, Asmaa; et al.
Abstract : Objective: Type 1 diabetes (T1D) is an autoimmune disease caused by the destruction of pancreatic β-cells producing insulin. Both T1D patients and animal models exhibit gut microbiota and mucosa alterations, although the exact cause for these remains poorly understood. We investigated the production of key cytokines controlling gut integrity, the abundance of segmented filamentous bacteria (SFB) involved in the production of these cytokines, and the respective role of autoimmune inflammation and hyperglycaemia. Design: We used several mouse models of autoimmune T1D as well as mice rendered hyperglycaemic without inflammation to study gut mucosa and microbiota dysbiosis. We analysed cytokine expression in immune cells, epithelial cell function, SFB abundance and microbiota composition by 16S sequencing. We assessed the role of anti-tumour necrosis factor α on gut mucosa inflammation and T1D onset. Results: We show in models of autoimmune T1D a conserved loss of interleukin (IL)-17A, IL-22 and IL-23A in gut mucosa. Intestinal epithelial cell function was altered and gut integrity was impaired. These defects were associated with dysbiosis including progressive loss of SFB. Transfer of diabetogenic T-cells recapitulated these gut alterations, whereas induction of hyperglycaemia with no inflammation failed to do so. Moreover, anti-inflammatory treatment restored gut mucosa and immune cell function and dampened diabetes incidence. Conclusion: Our results demonstrate that gut mucosa alterations and dysbiosis in T1D are primarily linked to inflammation rather than hyperglycaemia. Anti-inflammatory treatment preserves gut homeostasis and protective commensal flora reducing T1D incidence.